Sulfur-resistant methane dry reforming catalyst as well as preparation method and application thereof

By forming a Ni3P shell on a nickel-based catalyst and combining a nickel-aluminum bimetallic oxide matrix to form a core-shell structure of Ni@Ni3P, the problem of poisoning and inactivation of the catalyst under sulfur-containing conditions is solved, and an efficient and stable methane dry reforming reaction is achieved.

CN119657148AActive Publication Date: 2025-03-21BEIJING UNIV OF CHEM TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411835871.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing nickel-based methane dry reforming catalysts are prone to poisoning and inactivation under sulfur-containing conditions, resulting in a decrease in catalyst activity and an increase in operational complexity.

Method used

By forming a Ni3P shell on the surface of nickel particles, a core-shell structure of Ni@Ni3P is formed, and a nickel-aluminum bimetallic oxide matrix (NiAl-LDO) is combined to improve the catalyst's anti-sulfur poisoning ability and stability.

Benefits of technology

It realizes efficient conversion of CH4 and CO2 into synthesis gas in the presence of SO2, improves the stability and activity of the catalyst, reduces the sintering risk of the catalyst, and is suitable for high-temperature DRM reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657148A_ABST
    Figure CN119657148A_ABST
Patent Text Reader

Abstract

The invention provides a sulfur-resistant methane dry reforming catalyst as well as a preparation method and application thereof, the structural formula of the catalyst is Ni-coated Ni3P / NiAl-LDO, the active center of the catalyst is Ni-coated Ni3P composite nanoparticles uniformly dispersed on a NiAl-LDO carrier, and the particle size of the catalyst is 5-30nm. According to the present invention, the specific raw materials, the specific ratio and the specific preparation method are adopted to achieve the existence of the special core-shell structure in the catalyst, and the structure unexpectedly achieves the resistance to the poisoning of SO2 to Ni particles, such that the stability of the catalyst can be improved, the efficiency of converting CH4 and CO2 into the synthesis gas in the presence of SO2 is substantially improved, and the catalyst can be used for the industrial production. In addition, NiAl-LDO has very strong metal-carrier interaction, sintering of Ni in the reaction process can be inhibited, and the catalyst is more suitable for a DRM reaction needing high temperature, so that the catalyst has a great industrialization prospect; within the reaction time of 12 hours, the initial conversion rate of CH4 is less than or equal to 94, and the initial conversion rate of CO2 is less than or equal to 94.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sulfur-resistant catalysts, and in particular to a sulfur-resistant methane dry reforming catalyst, a preparation method and uses thereof, and more particularly to a sulfur-resistant nickel-based methane dry reforming catalyst with a core-shell structure, a preparation method and uses thereof. Background Art

[0002] Carbon dioxide (CO2), as the world's largest greenhouse gas, stays in the atmosphere for a long time and contributes greatly to the rise in global temperatures. Methane (CH4) is the world's second largest greenhouse gas after carbon dioxide and is more active in the atmosphere than carbon dioxide. Methane in the global atmosphere is a trace gas, and a slight increase in its emissions will lead to a significant increase in the methane content in the atmosphere. Methane has a significant greenhouse effect, and its role in promoting global warming in the short term cannot be underestimated. Excessive emissions of CO2 and CH4 are the most important cause of global warming, triggering a series of ecological problems, such as melting glaciers and rising sea levels threatening coastal areas; frequent extreme climate events, floods, droughts, heat waves and other disasters bring huge challenges to human life.

[0003] Dry Reforming of Methane (DRM) technology can convert these two greenhouse gases into valuable industrial syngas raw materials with an equimolar H2 / CO ratio, which can then be prepared into high-value chemicals and liquid fuels through the Fischer-Tropsch synthesis process. DRM technology can turn waste into treasure, achieving effective utilization of resources while reducing greenhouse gas emissions, and is of great significance for mitigating global warming. Catalysts are the core of methane dry reforming technology. Precious metals have high activity and stability, but their high prices limit their widespread application. Non-precious metal nickel has industrial application prospects in DRM technology due to its strong ability to break CH bonds and CO bonds.

[0004] However, nickel-based catalysts will inevitably have problems of sintering and carbon deposition during use. At present, the research on DRM catalysts is also mainly focused on solving the problem of decreased activity due to sintering and carbon deposition of nickel particles. However, the actual conditions of DRM inevitably involve the presence of sulfur-containing compounds, and there is less research on the negative effects of sulfides. Sulfur species easily bind to the metal active sites of the catalyst to form a stable metal-sulfur bond (Me-S), resulting in catalyst poisoning. The current DRM is mainly focused on solving the deactivation problem of Ni catalysts due to sintering and carbon deposition of Ni particles, while less attention is paid to the negative effects of sulfur poisoning. Obviously, in metal catalysts, active Ni sites are highly sensitive to sulfur species, and even exposure to sulfur at ppm levels may cause partial or complete deactivation of Ni-based catalysts. At present, DRM technology usually requires a desulfurization process, which makes the operation process complicated and adds additional costs. Therefore, providing a DRM catalyst with high activity, high selectivity and resistance to sulfur poisoning has become a technical problem to be solved urgently.

[0005] CN118904347A discloses a carbon-resistant nickel-based catalyst for methane carbon dioxide dry reforming, a preparation method and its application. The patent combines innovative formulas and processes to prepare a carbon-resistant nickel-based catalyst made of metal organic framework material-derived nanotubes as precursors and impregnated with nickel salts and zirconium salts. In the DRM reaction, the catalyst exhibits excellent carbon-resistant performance, while the catalytic activity is highly maintained, the CO2 conversion rate is stable at about 90%, and the CH4 conversion rate is maintained at more than 93%, effectively overcoming the difficulties of carbon deposition and deactivation of traditional nickel-based catalysts in the reaction, and the preparation process is simple, the conditions are mild, and it has good industrial application potential. However, it is still necessary to continue to conduct in-depth research and improvement in reducing carbon deposition, expanding the adaptability of reaction conditions, and comprehensively evaluating long-term stability.

[0006] Hu et al. loaded BaTiO3 on the surface of γ-Al2O3 by the sol-gel method to synthesize composite carriers BaTiO3 / γ-Al2O3 with different BaTiO3 mass percentages, and used XRD and IR techniques to study the structure of the composite carrier BaTiO3 / γ-Al2O3, and investigated the anti-coking and stability properties of the nickel-based catalyst Ni / BaTiO3 / γ-Al2O3 loaded on the composite carrier in the CH4-CO2 reforming reaction; the results showed that: BaTiO3 particles were dispersed on the surface of γ-Al2O3 in a discontinuous manner, resulting in a relative weakening of the electron donation intensity of the Ni / BaTiO3 / γ-Al2O3 catalyst after in-situ hydrogen reduction, inhibiting the disproportionation reaction of CO in the CH4-CO2 reforming process, and the anti-coking and stability properties of the Ni / 25.4% BaTiO3 / γ-Al2O3 catalyst at a lower reforming reaction temperature of 700℃ were significantly better than those of Ni / BaTiO3 and Ni / γ-Al2O3 catalysts. However, there are still problems such as unclear applicability under different temperature conditions, the catalyst stability needs to be further improved, and the catalyst trial scope needs to be further expanded. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a sulfur-resistant methane dry reforming catalyst with hydrotalcite as a precursor: a nickel aluminum hydrotalcite (NiAl-LDH) precursor is calcined in an inert gas atmosphere to obtain a layered bimetallic oxide (NiAl-LDO) matrix, and NiAl-LDO is mixed with sodium hypophosphite and calcined in an inert gas atmosphere to obtain the catalyst. Due to the phosphating effect, a layer of Ni3P shell is formed on the surface of Ni particles, and its active component has a core-shell structure of Ni@Ni3P, which can resist the poisoning of Ni particles by SO2, thereby realizing efficient and stable conversion of CH4 and CO2 into synthesis gas in the presence of SO2. In addition, NiAl-LDO has a strong metal-carrier interaction, which can inhibit the sintering of Ni during the reaction. The specific technical scheme is as follows:

[0008] A sulfur-resistant methane dry reforming catalyst, the catalyst is composed of a nickel-aluminum bimetallic oxide matrix carrying a core-shell structure active center Ni@Ni3P, the structural formula is Ni@Ni3P / NiAl-LDO, in the catalyst, the molar ratio of P, Al, Ni is (0.2-0.8):(0.4-0.6):1; in the XRD spectrum of the catalyst, characteristic diffraction peaks of Ni3P (031), (231), (330), (112), (240), (202), (141), (222), (132), (611), (233) appear at 2θ angles of 36.4°, 41.8°, 42.8°, 43.6°, 45.2°, 46.0°, 46.6°, 50.6°, 52.7°, 66.9°, 75.3°;

[0009] Furthermore, HRTEM characterization shows that a specific Ni@Ni3P core-shell structure exists in the catalyst.

[0010] Furthermore, in TEM characterization, the ratio of P to Ni in the catalyst is (0.2-0.8):1, and it can be observed that the active center of the catalyst is Ni@Ni3P composite nanoparticles uniformly dispersed on the NiAl-LDO carrier, and the particle size of the catalyst is 5-30 nm.

[0011] Furthermore, ICP test shows that, based on the total weight of the catalyst, the Ni content in the active center Ni@Ni3P is 40-60wt% in terms of metal element.

[0012] Furthermore, the BET test showed that the specific surface area of ​​the catalyst was 60.9-75.5 m 2 / g.

[0013] Furthermore, SEM characterization shows that the catalyst always maintains the morphology of hexagonal nanosheets unique to hydrotalcite.

[0014] A method for preparing a sulfur-resistant methane dry reforming catalyst, the method comprising the following steps:

[0015] Step 1: Preparation of NiAl-LDH

[0016] Take Ni(NO3)2·6H2O and Al(NO3)3·9H2O and place them in a beaker, add deionized water and stir evenly to obtain a metal salt solution, in which Ni 2+ / Al 3+The molar ratio of urea and NH4F is (1-4):1; urea and NH4F are placed in a beaker, deionized water is added and stirred to obtain a mixed alkaline solution, wherein the molar ratio of urea and NH4F is (2.5-10):1, the metal salt solution and the mixed alkaline solution are poured into a hydrothermal kettle, statically crystallized at 60-120°C for 4-24h to obtain a precipitate, the precipitate is filtered, washed, and then put into an oven for drying, the temperature is set to 60-80°C, and the time is 12-24h to obtain NiAl-LDH;

[0017] Step 2: Preparation of NiAl-LDO

[0018] Take the NiAl-LDH obtained in step 1, calcine it in an inert gas atmosphere, the starting temperature is room temperature, the temperature is increased to 800-1000° C. at a heating rate of 2-10° C. / min, the calcination time is 2-5 h, and the inert gas flow rate is 10-40 mL / min to obtain NiAl-LDO;

[0019] Step 3: Preparation of sulfur-resistant methane dry reforming catalyst

[0020] The NiAl-LDO obtained in step 2 is mixed with sodium hypophosphite, wherein the molar ratio of P to Ni is (0.1-1): 1, and calcined under an inert gas atmosphere, with the starting temperature being room temperature, and the temperature is raised to 800-1000° C. at a heating rate of 2-10° C. / min, the calcination time is 2-5 h, and the inert gas flow rate is 10-40 mL / min to obtain the sulfur-resistant methane dry reforming catalyst, which is recorded as Ni@Ni3P / NiAl-LDO.

[0021] Further, in step 1, the XRD spectrum of the NiAl-LDH clearly observed the characteristic diffraction peaks of (003), (006), (012), (015), (018), (1010), (0111), (110), (113), (1013) and (116) of nickel aluminum hydrotalcite at 2θ angles of 11.3°, 22.8°, 34.7°, 39.1°, 46.4°, 52.2°, 55.5°, 60.6°, 61.9°, 62.5 and 65.7°, and no other diffraction peaks appeared except the characteristic peaks of hydrotalcite.

[0022] Furthermore, in step 2, the inert gas is any one of N2, Ar, and He.

[0023] A method for using the above-mentioned sulfur-resistant methane dry reforming catalyst for methane dry reforming reaction, taking the catalyst, granulating it into 40-60 mesh, loading it into a reactor, the reaction temperature is 600-800°C, first using H2 to purge for 0.5-2h, the flow rate of H2 is 30-50mL / min / g, and then passing the raw gas containing SO2 into the reactor, the raw gas is a mixed gas of CH4 and CO2, the reaction pressure is set to 0.1-2MPa, and the space velocity is set to 3000-12000mL·g -1 ·h -1 The reaction time is 12-100h, and the products are CO and H2, among which the initial conversion rate of CH4 is ≤94, and the initial conversion rate of CO2 is ≤94.

[0024] Furthermore, in the mixed gas, based on the total volume of the mixed gas as a percentage, the volume proportions of SO2, CH4, and CO2 are (1-10):(100-5000):(100-5000).

[0025] Furthermore, the reactor is a fixed bed reactor with a length of 200-350 mm and an inner diameter of 5-10 mm.

[0026] The beneficial effects of the present invention are as follows:

[0027] 1. In the catalyst of the present invention, sodium hypophosphite is cleverly introduced to form a Ni3P shell on the surface of the Ni particles, thereby encapsulating the Ni metal atoms, so that the active component of the catalyst of the present invention has a core-shell structure of Ni@Ni3P. This structure unexpectedly achieves resistance to SO2 poisoning of Ni particles, thereby improving the stability of the catalyst and greatly improving the efficiency of converting CH4 and CO2 into synthesis gas in the presence of SO2. In addition, NiAl-LDO has a strong metal-carrier interaction, which can inhibit the sintering of Ni during the reaction, making it more suitable for DRM reactions requiring high temperatures, so that the catalyst of the present invention has great industrial prospects;

[0028] 2. The catalyst preparation method of the present invention is relatively simple, and the raw material cost is low. The NiAl-LDH precursor is prepared by a hydrothermal method using common metal salts and alkaline solutions, and then the target catalyst is obtained through the steps of calcination and mixing with sodium hypophosphite and then calcination. The whole process does not require complicated equipment and harsh reaction conditions, is easy to large-scale industrial production, and is conducive to reducing production costs.

[0029] 3. The catalyst of the present invention exhibits good stability under the condition of raw gas containing SO2. In the methane dry reforming reaction, even if it is exposed to a sulfur-containing environment for a long time (12-100 hours), the activity of the catalyst can still be maintained, and the conversion rate of CH4 and CO2 does not decrease significantly during the reaction. This provides an effective solution for treating sulfur-containing greenhouse gases in actual industrial production, avoiding the problems of increased costs and production interruptions caused by frequent replacement of catalysts due to catalyst deactivation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 XRD diagram of the sample of the present invention

[0031] Figure 1 (a) is the XRD test result of NiAl-LDH prepared by the urea method. The characteristic diffraction peaks of (003), (006), (012), (015), (018), (1010), (0111), (110), (113), (1013) and (116) of hydrotalcite are clearly observed at 2θ angles of 11.3°, 22.8°, 34.7°, 39.1°, 46.4°, 52.2°, 55.5°, 60.6°, 61.9°, 62.5 and 65.7°. Except for the characteristic peaks of hydrotalcite, no other diffraction peaks appear, indicating that a hydrotalcite sample with complete crystal form and no impurities is prepared;

[0032] Figure 1(b) in the figure are the products after calcination with different proportions of sodium hypophosphite, red phosphorus and without adding phosphorus source, respectively, recorded as: Ni@Ni3P / NiAl-LDO, Ni2P / NiAl-LDO, and NiAl-LDO; the top curve is the XRD diagram of NiAl-LDO, and the characteristic peaks of Ni (111), (200), and (220) are only observed at 2θ angles of 44.5°, 51.8°, and 76.4°; the second one from the top is the XRD diagram of Ni2P / NiAl-LDO with red phosphorus added, and Ni2P (111), (201), (210), (300), (211), and (310) are observed at 2θ angles of 40.8°, 44.6°, 47.3°, 54.2°, 54.9°, 66.2°, 72.7°, and 76.7°. , (311), (400) characteristic peaks; the three curves arranged below are the XRD patterns of Ni@Ni3P / NiAl-LDO. The characteristic peaks of Ni@Ni3P(031), (231), (330), (112), (240), (202), (141), (222), (132), (611), (233) and the characteristic peaks of Ni(111), (200), (220) were observed at 2θ angles of 36.4°, 41.8°, 42.8°, 43.6°, 45.2°, 46.0°, 46.6°, 50.6°, 52.7°, 66.9°, 75.3° and 44.5°, 51.8°, 76.4°. Therefore, the present application can realize the presence of a specific core-shell structure in the catalyst only under specific raw materials, specific ratios and specific preparation methods.

[0033] Figure 2 SEM image of the sample of the present invention

[0034] Figure 2 (a) is the product Ni@Ni3P / NiAl-LDO after calcination using sodium hypophosphite as the phosphorus source. Figure 2 (b) is the product Ni2P / NiAl-LDO after calcination using red phosphorus as the phosphorus source. Figure 2 (c) is the product NiAl-LDO after calcination without adding phosphorus source. It can be seen that all catalyst samples maintain the morphology of hexagonal nanosheets of hydrotalcite.

[0035] Figure 3 TEM image of the sample of the present invention

[0036] Figure 3 (a) is the product Ni@Ni3P / NiAl-LDO after calcination using sodium hypophosphite as the phosphorus source. It can be seen that the size of the metal particles is 5.4-28.1nm; Figure 3(b) is the product Ni2P / NiAl-LDO after calcination using red phosphorus as the phosphorus source. It can be seen that the size of the metal particles is 5.1-25.2nm; Figure 3 (c) is the product NiAl-LDO after calcination without adding phosphorus source. It can be seen that the size of the metal particles is 5.2-36.5nm.

[0037] Figure 4 HRTEM image of the sample of the present invention

[0038] Figure 4 (a) is the product Ni@Ni3P / NiAl-LDO after calcination using sodium hypophosphite as the phosphorus source. It can be seen that the metal particles have an obvious core-shell structure, in which the core is Ni and the shell is Ni3P. Figure 4 (b) is the product Ni2P / NiAl-LDO after calcination using red phosphorus as the phosphorus source. Only a single metal particle can be seen on the carrier, and the metal particle is Ni2P. Figure 4 (c) is the product NiAl-LDO after calcination without adding phosphorus source. Similarly, only a single metal particle can be seen on the carrier, and the metal particle is Ni.

[0039] Figure 5 CH4 and CO2 conversion rate diagram

[0040] Figure 5 The curves P:Ni=0.26:1, P:Ni=0.5:1, and P:Ni=0.8:1 are the products Ni@Ni3P / NiAl-LDO with core-shell structure obtained by calcining with sodium hypophosphite as the phosphorus source. The conversion rates of CH4 and CO2 are high, and there is no obvious decrease in performance within the reaction time of 12h. Figure 5 The curve P:Ni=1:1 in the figure is the supported catalyst Ni2P / NiAl-LDO obtained by calcining red phosphorus as the phosphorus source. The conversion rate is lower than that of Ni@Ni3P / NiAl-LDO, and the conversion rates of CH4 and CO2 decrease within the reaction time of 12h, indicating that the sample is partially deactivated. Figure 5 The curve P:Ni=0:1 in the figure is the supported catalyst NiAl-LDO obtained by calcination without adding phosphorus source. The conversion rate of CH4 and CO2 is significantly lower than that of Ni@Ni3P / NiAl-LDO. Within the reaction time of 12h, the conversion rate dropped significantly, and the sample was severely deactivated. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be described in detail below in conjunction with specific embodiments of the present invention. The described embodiments are only a part of the present invention, and the present invention is not limited to the embodiments described below.

[0042] Example 1

[0043] A sulfur-resistant methane dry reforming catalyst, wherein the molar ratio of P, Al and Ni in the catalyst is 0.26:0.5:1;

[0044] Step 1: Preparation of NiAl-LDH

[0045] 3.8 g of Ni(NO3)2 6H2O and 1.6 g of Al(NO3)3 9H2O were weighed and dissolved in 350 mL of deionized water, and stirred to obtain a metal salt solution; 5.1 g of urea and 0.9 g of NH4F were weighed and dissolved in 350 mL of deionized water, and stirred to obtain a mixed alkali solution; the metal salt solution and the mixed alkali solution were poured into a hydrothermal kettle at the same time, the crystallization temperature was controlled to be 90°C, the crystallization time was controlled to be 4 h, and the precipitate was filtered, washed, and dried in an oven at 60°C for 12 h to obtain NiAl-LDH;

[0046] Step 2: Preparation of NiAl-LDO

[0047] Weigh 1 g of NiAl-LDH obtained in step 1, calcine it under H2 atmosphere for 5 h, set the temperature to 500 °C, the starting temperature to room temperature, the heating rate to 2 °C / min, and the gas flow rate to 30 mL / min to obtain NiAl-LDO;

[0048] Step 3: Preparation of sulfur-resistant methane dry reforming catalyst

[0049] Weigh 1 g of NiAl-LDO obtained in step 2 and 0.28 g of sodium hypophosphite and mix them evenly, calcine them under H2 atmosphere for 5 h, set the temperature to 1000° C., the starting temperature to room temperature, the heating rate to 10° C. / min, and the gas flow rate to 30 mL / min, to obtain the sulfur-resistant methane dry reforming catalyst 1, recorded as Ni@Ni3P / NiAl-LDO;

[0050] Example 2

[0051] A sulfur-resistant methane dry reforming catalyst, wherein the molar ratio of P, Al and Ni in the catalyst is 0.5:0.5:1;

[0052] Step 1: Preparation of NiAl-LDH

[0053] Weigh 4.0 g of Ni(NO3)2 6H2O and 1.8 g of Al(NO3)3 9H2O, dissolve them in 350 mL of deionized water, and stir them to obtain a metal salt solution; weigh 5.1 g of urea and 0.9 g of NH4F, dissolve them in 350 mL of deionized water, and stir them to obtain a mixed alkali solution; pour the metal salt solution and the mixed alkali solution into a hydrothermal kettle at the same time, control the crystallization temperature to 90°C, the crystallization time to 4 h, filter and wash the precipitate, and then dry it in an oven at 60°C for 12 h to obtain NiAl-LDH;

[0054] Step 2: Preparation of NiAl-LDO

[0055] Weigh 1 g of NiAl-LDH obtained in step 1, calcine it under H2 atmosphere for 5 h, set the temperature to 500 °C, the starting temperature to room temperature, the heating rate to 2 °C / min, and the gas flow rate to 30 mL / min to obtain NiAl-LDO;

[0056] Step 3: Preparation of sulfur-resistant methane dry reforming catalyst

[0057] Weigh 1 g of NiAl-LDO obtained in step 2 and 0.53 g of sodium hypophosphite and mix them evenly, calcine them for 5 h in a H2 atmosphere, set the temperature to 1000°C, the starting temperature to room temperature, the heating rate to 10°C / min, and the gas flow rate to 30 mL / min to obtain the sulfur-resistant methane dry reforming catalyst 2, recorded as Ni@Ni3P / NiAl-LDO;

[0058] Example 3

[0059] A sulfur-resistant methane dry reforming catalyst, wherein the molar ratio of P, Al and Ni in the catalyst is 0.8:0.5:1;

[0060] Step 1: Preparation of NiAl-LDH

[0061] Weigh 4.2g of Ni(NO3)2 6H2O and 2g of Al(NO3)3 9H2O, dissolve them in 350mL of deionized water, and stir them to obtain a metal salt solution; weigh 5.1g of urea and 0.9g of NH4F, dissolve them in 350mL of deionized water, and stir them to obtain a mixed alkali solution; pour the metal salt solution and the mixed alkali solution into a hydrothermal kettle at the same time, control the crystallization temperature to 90°C, the crystallization time to 4h, filter and wash the precipitate, and then dry it in an oven at 60°C for 12h to obtain NiAl-LDH;

[0062] Step 2: Preparation of NiAl-LDO

[0063] Weigh 1 g of NiAl-LDH obtained in step 1, calcine it under H2 atmosphere for 5 h, set the temperature to 500 °C, the starting temperature to room temperature, the heating rate to 2 °C / min, and the gas flow rate to 30 mL / min to obtain NiAl-LDO;

[0064] Step 3: Preparation of sulfur-resistant methane dry reforming catalyst

[0065] Weigh 1 g of NiAl-LDO obtained in step 2 and 0.85 g of sodium hypophosphite and mix them evenly, calcine them under H2 atmosphere for 5 h, set the temperature to 1000° C., the heating rate to 10° C. / min, and the gas flow rate to 30 mL / min, to obtain the sulfur-resistant methane dry reforming catalyst 3, recorded as Ni@Ni3P / NiAl-LDO;

[0066] Comparative Example 1

[0067] A supported nickel phosphide DRM catalyst derived from hydrotalcite, wherein the molar ratio of P, Al and Ni in the catalyst is 1:0.5:1.

[0068] Step 1: Preparation of NiAl-LDH

[0069] Weigh 2.6 g of Ni(NO3)2 6H2O and 1.2 g of Al(NO3)3 9H2O, dissolve them in 350 mL of deionized water, and stir them to obtain a metal salt solution; weigh 5.1 g of urea and 0.9 g of NH4F, dissolve them in 350 mL of deionized water, and stir them to obtain a mixed alkali solution; pour the metal salt solution and the mixed alkali solution into a hydrothermal kettle at the same time, control the crystallization temperature to 90°C, the crystallization time to 4 h, filter and wash the precipitate, and then dry it in an oven at 60°C for 12 h to obtain NiAl-LDH;

[0070] Step 2: Preparation of NiAl-LDO

[0071] Weigh 1 g of NiAl-LDH obtained in step 1, calcine it under H2 atmosphere for 5 h, set the temperature to 500 °C, the starting temperature to room temperature, the heating rate to 2 °C / min, and the gas flow rate to 30 mL / min to obtain NiAl-LDO;

[0072] Step 3: Preparation of supported nickel phosphide DRM catalyst derived from hydrotalcite

[0073] Weigh 1 g of NiAl-LDO obtained in step 2 and 0.31 g of red phosphorus and mix them evenly, and calcine them under H2 atmosphere for 5 h, setting the temperature to 1000°C, the heating rate to 5°C / min, and the gas flow rate to 30 mL / min to obtain a hydrotalcite-derived supported nickel phosphide DRM catalyst 4, recorded as Ni2P / NiAl-LDO;

[0074] Comparative Example 2

[0075] NiAl-LDO was used as the catalyst, and the molar ratio of P, Al, and Ni in the catalyst was 0:0.4:1;

[0076] Step 1: Preparation of NiAl-LDH

[0077] Weigh 4.2g of Ni(NO3)2 6H2O and 1.7g of Al(NO3)3 9H2O, dissolve them in 350mL of deionized water, and stir them to obtain a metal salt solution; weigh 5.1g of urea and 0.9g of NH4F, dissolve them in 350mL of deionized water, and stir them to obtain a mixed alkali solution; pour the metal salt solution and the mixed alkali solution into a hydrothermal kettle at the same time, control the crystallization temperature to 90°C, the crystallization time to 4h, filter and wash the precipitate, and then dry it in an oven at 60°C for 12h to obtain NiAl-LDH;

[0078] Step 2: Preparation of NiAl-LDO

[0079] Weigh 1 g of NiAl-LDH obtained in step 1, and calcine it under H2 atmosphere for 5 h, setting the temperature to 500°C, the heating rate to 2°C / min, and the gas flow rate to 30 mL / min to obtain NiAl-LDO, which is recorded as catalyst 5;

[0080] Methane and carbon dioxide dry reforming reaction: tested in a fixed bed reactor with a length of 200 mm and an inner diameter of 8 mm, 0.1 g of the sieved catalyst 1-5 was weighed and loaded into a stainless steel reaction tube, fixed with 2-4 μm quartz wool, the reaction temperature of the test was controlled by an intelligent cycle thermostat, the component content of the reaction product was detected by gas chromatography GC-2014, and the tail gas was discharged after being treated by an absorption device;

[0081] Among them, the composition of the reaction gas is: 500mg / m 3 SO2, 100000mg / m 3 CH4, 100000mg / m 3 CO2 composition, N2 as the balance gas, reaction space velocity of 6000mL·g -1 ·h -1 ; Set the reaction pressure to normal pressure, the reaction temperature to 800℃, and the reaction time to 12h.

[0082] Table 1. Examples and comparative examples show the conversion rates of catalytic dry reforming reactions of methane and carbon dioxide.

[0083] Sample No. P / Ni molar ratio <![CDATA[Initial conversion rate of CH4]]> <![CDATA[Initial conversion rate of CO2]]> 12h catalyst activity Catalyst 1 0.26:1 92% 92% No obvious inactivation Catalyst 2 0.5:1 94% 94% No obvious inactivation Catalyst 3 0.8:1 91% 91% No obvious inactivation Catalyst 4 1:1 90% 90% Inactivation Catalyst 5 0:1 88% 90% Inactivation

[0084] As can be seen from Table 1, the catalyst Ni@Ni3P / NiAl-LDO with a core-shell structure obtained by calcining sodium hypophosphite as a phosphorus source in this embodiment has a high initial conversion rate of CH4 and CO2, and there is no obvious decline in performance within a reaction time of 12 hours; the supported catalyst Ni2P / NiAl-LDO obtained by calcining red phosphorus as a phosphorus source in Comparative Example 1 has a lower conversion rate than the catalysts of Examples 1-3, and the catalyst is significantly deactivated within a reaction time of 12 hours; Comparative Example 2 is a supported catalyst NiAl-LDO obtained by calcining without adding a phosphorus source, and the conversion rate is lower than the catalyst of the present invention, and the catalyst is severely deactivated within a reaction time of 12 hours. This is because in the catalyst of the present invention, by cleverly introducing sodium hypophosphite, phosphating occurs on the surface of Ni particles to form a Ni3P shell, forming a wrapping of Ni metal atoms, so that the active component of the catalyst of the present invention has a Ni@Ni3P core-shell structure, which unexpectedly achieves resistance to SO2 poisoning of Ni particles, thereby improving the stability of the catalyst and greatly improving the efficiency of converting CH4 and CO2 into synthesis gas in the presence of SO2. In addition, NiAl-LDO has a strong metal-carrier interaction, which can inhibit the sintering of Ni during the reaction, making it more suitable for DRM reactions requiring high temperatures, so that the catalyst of the present invention has great industrial prospects.

[0085] The above-mentioned embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of the invention patent protection. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A sulfur-resistant methane dry reforming catalyst, characterized in that: The catalyst has a specific core-shell structure active center Ni@Ni3P, and the active center is supported on a nickel-aluminum bimetallic oxide matrix. The structural formula of the catalyst is Ni@Ni3P / NiAl-LDO. In the catalyst, the molar ratio of P, Al and Ni is (0.2-0.8):(0.4-0.6):

1. In the XRD spectrum of the catalyst, characteristic diffraction peaks of Ni@Ni3P (031), (231), (330), (112), (240), (202), (141), (222), (132), (611) and (233) appear at 2θ angles of 36.4°, 41.8°, 42.8°, 43.6°, 45.2°, 46.0°, 46.6°, 50.6°, 52.7°, 66.9° and 75.3°. The particle size of the catalyst is 5-30 nm; based on the total weight of the catalyst, the Ni content in the active center Ni@Ni3P is 40-60 wt % in terms of metal element; the specific surface area of ​​the catalyst is 60.9-75.5 m 2 / g; the catalyst maintains the morphology of hexagonal nanosheets of hydrotalcite.

2. A method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 1, characterized in that: The method comprises the following steps: Step 1: Preparation of NiAl-LDH Ni(NO3)2·6H2O and Al(NO3)3·9H2O are placed in a beaker, deionized water is added and stirred to obtain a metal salt solution, urea and NH4F are placed in a beaker, deionized water is added and stirred to obtain a mixed alkali solution, the metal salt solution and the mixed alkali solution are poured into a hydrothermal kettle, statically crystallized at 60-120°C for 4-24h to obtain a precipitate, the precipitate is filtered, washed, and then dried in an oven at a temperature of 60-80°C for 12-24h to obtain NiAl-LDH; Step 2: Preparation of NiAl-LDO Take the NiAl-LDH obtained in step 1, calcine it in an inert gas atmosphere, the starting temperature is room temperature, the temperature is increased to 800-1000° C. at a heating rate of 2-10° C. / min, the calcination time is 2-5 h, and the inert gas flow rate is 10-40 mL / min to obtain NiAl-LDO; Step 3: Preparation of sulfur-resistant methane dry reforming catalyst The NiAl-LDO obtained in step 2 is mixed with sodium hypophosphite and calcined in an inert gas atmosphere. The starting temperature is room temperature, and the temperature is raised to 800-1000° C. at a heating rate of 2-10° C. / min. The calcination time is 2-5 h, and the inert gas flow rate is 10-40 mL / min to obtain the sulfur-resistant methane dry reforming catalyst, which is recorded as Ni@Ni3P / NiAl-LDO.

3. The method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 2, characterized in that: In step 1, the XRD spectrum of the NiAl-LDH observed characteristic diffraction peaks of (003), (006), (012), (015), (018), (1010), (0111), (110), (113), (1013) and (116) of nickel aluminum hydrotalcite at 2θ angles of 11.3°, 22.8°, 34.7°, 39.1°, 46.4°, 52.2°, 55.5°, 60.6°, 61.9°, 62.5 and 65.7°. Except for the characteristic peaks of hydrotalcite, no other diffraction peaks appeared.

4. The method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 2, characterized in that: In step 1, in the metal salt solution, Ni 2+ / Al 3+ The molar ratio is (1-4):

1.

5. The method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 2, characterized in that: In step 1, in the mixed alkaline solution, the molar ratio of urea to NH4F is (2.5-10):

1.

6. The method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 2, characterized in that: In step 2, the inert gas is any one of N2, Ar, and He.

7. The method for preparing the sulfur-resistant methane dry reforming catalyst according to claim 2, characterized in that: In step 3, NiAl-LDO is mixed with sodium hypophosphite, wherein the molar ratio of P to Ni is (0.1-1):

1.

8. A method for methane dry reforming reaction using the sulfur-resistant methane dry reforming catalyst according to claim 1, characterized in that: The catalyst is taken, granulated into 40-60 mesh, and loaded into a reactor. The reaction temperature is 600-800°C. H2 is first used for purging for 0.5-2h, and the flow rate of H2 is 30-50mL / min / g. Then, the raw gas containing SO2 is introduced into the reactor. The raw gas is a mixed gas of CH4 and CO2. The reaction pressure is set to 0.1-2MPa, and the space velocity is set to 3000-12000mL·g -1 ·h -1 , the reaction time is 12-100h, wherein the initial conversion rate of CH4 is ≤94, and the initial conversion rate of CO2 is ≤94.

9. The method for using the sulfur-resistant methane dry reforming catalyst according to claim 8 for methane dry reforming reaction, characterized in that: In the mixed gas, based on the total volume of the mixed gas as a percentage, the volume proportions of SO2, CH4, and CO2 are (1-10):(100-5000):(100-5000).

10. The method for using the sulfur-resistant methane dry reforming catalyst according to claim 8 for methane dry reforming reaction, characterized in that: The reactor is a fixed bed reactor with a length of 200-350 mm and an inner diameter of 5-10 mm.

Citation Information

Patent Citations

  • Co2P / Ni2P / Al2O3 / NF multistage structure composite electrode and production method thereof

    CN110257859A

  • Supported nickel phosphide catalyst for preparing hydrogenated petroleum resin and preparation method of supported nickel phosphide catalyst

    CN112206795A

  • Supported nickel phosphide catalyst for petroleum resin hydrogenation and preparation method thereof

    CN114308087A

  • Application of Ni3P / SiO2 catalyst in DBD plasma methane dry reforming

    CN116374954A

  • Non-noble metal phosphide catalyst as well as preparation method and application thereof

    CN118932378A